SPATIAL MEMORY AND HISTOMORPHOLOGICAL CHANGES INDUCED BY SUBCHRONIC NITROCELLULOSE INHALATION IN MICE: ROLE OF DEXAMETHASONE IN THE CEREBRUM - Balogun, Olubunmi; Kalanjati, Viskasari P (Universitas Airlangga, 2025)
Introduction: Thinners are toxic substances used as organic solvents. Adolescents (11%) use thinners as inhalants regularly, which is linked to brain damage and learning deficits. This study looked at the effects of thinner inhalation in adult male mice and dexamethasone's anti-inflammatory effects on pyramidal neurons and glia. Aim: To investigate dexamethasone's anti-inflammatory effects on nitrocellulose inhalation. Methods: Forty mice were used; group one served as a control; group two was exposed to 1200ppm nitrocellulose in a whole-body inhalation chamber for 42 days; group three was injected with 2.5mg/kg dexamethasone twice weekly; and group four received nitrocellulose inhalation daily and dexamethasone twice weekly. Neurobehavioral study for learning and memory was conducted before sacrifice. Brains were harvested and processed for histology and biochemical activities of MDA and IL-6. Analysis of data was done using Graphpad Prism 8.4.3 with level of significance at P<0.05. Results: Indices of learning and memory in the nitrocellulose group were reduced escape latency and duration spent in the quadrant but not in the control or dexamethasone group (P=0.009). The MDA and IL-6 levels were higher in the nitrocellulose group compared to control and dexamethasone groups (P=0.02; P=0.03, respectively). Density of pyramidal neurons in layer 5 and 6 was significantly lower in the nitrocellulose treated groups compared to control and dexamethasone (P<0.0001). Conclusion: Dexamethasone reduced neuronal and glial cell damages in the pre-frontal cortex, accompanied with spatial learning and memory improvement.